Does Delayed Cord Clamping Improve Long-Term (≥4 Months) Neurodevelopment in Term Babies? A Systematic Review and a Meta-Analysis of Randomized Clinical Trials - Xodo, Serena; Xodo, Luigi; Baccarini, Giovanni; Driul, Lorenza; Londero, Ambrogio P. (Frontiers in Pediatrics, 2021)
Background. Recently, the literature suggested that placental transfusion facilitated by delayed cord clamping (DCC), besides having benefits on hematological parameters, might improve the infants’ brain development. Objective. The present review primarily evaluates the Ages and Stages Questionnaire (ASQ) total score mean difference (MD) at long-term follow-up (≥4 months) comparing DCC (>90 or >180 seconds) to early cord clamping (ECC). Secondary aims consisted of evaluating the ASQ domains’ MD and the results obtained from other methods adopted to evaluate the infants’ neurodevelopment. Methods. MEDLINE, Scopus, Cochrane, and ClinicalTrials.gov databases were searched (up to 2nd November 2020) for systematic review and meta-analysis. All randomized controlled trials (RCTs) of term singleton gestations received DCC or ECC. Multiple pregnancies, preterm delivery, non-randomized studies, and articles in languages other than English were excluded. The included studies were assessed for bias and quality. ASQ data were pooled stratified by time to follow up. Results. This meta-analysis of 4 articles from 3 RCTs includes 765 infants with four-month follow-up and 672 with 12 months follow-up. Primary aim (ASQ total score) pooled analysis was possible only for 12 months follow-up, and no differences were found between DCC and ECC (MD 1.1; CI.95: -5.1; 7.3). DCC approach significantly improves infants’ communication domains (MD 0.6; CI.95: 0.1; 1.1) and personal-social assessed (MD 1.0; CI.95: 0.3; 1.6) through ASQ at 12 months follow-up. Surprisingly, the four-month ASQ personal social domain (MD -1.6; CI.95: -2.8; -0.4) seems to be significantly lower in the DCC group than in the ECC group. Conclusions. DCC, a simple, non-interventional, and cost-effective approach, might improve the long-term infants’ neurological outcome. Single-blinding and limited studies number were the main limitations. Further research should be performed to confirm these observations, ideally with RCTs adopting standard methods to assess infants’ neurodevelopment. Trial registration. NCT01245296 NCT01581489 NCT02222805 NCT01620008 IRCT201702066807N19 NCT02727517